STRATEGI LIVE STREAMING DALAM MENDORONG GERAKAN BANGGA BUATAN INDONESIA - Rakhmah, Khaerunnisa; Yakob, Freddy; Juniati, Rifkah Kusmita (Kinesik, 2024)
Indonesia has entered a massive digitalization round. As a platform to bring together buyers and sellers, the growing need for the Indonesian people. Various vocational services are scrambling to be the best of service, price, and security. This development is followed by a social media role that is no longer a hub for relationships but a place of marketing and branding. One of the highest contents nowadays is a live stream. Information management and access that is so quick and easy to give anyone a chance to do this live stream. Live streaming behavior becomes a social media strategy that has a very broad impact on people's interest in goods and services that are offered. This doubtless affected his productivity and increased his rise domino's. In addition, Indonesia, which is now preparing a campaign of investment in Indonesia, is expected to make us buy local products. This empowerment would stimulate a micro-, small, and medium-scale (SMSE) venture that was ravaged by the previous pandemic. With this live stream it is expected to help SMSE to increase public interest, expand the network of product marketing, improve the sale of products with good quality, and have an impact on national economic empowerment